A comparative study of algorithms for level scheduling in just-in-time production systems - Medhi, Santanoo; Pandey, P. C.; Tabucanon, Mario T.; Nagarur, Nagendra N.; NORAD (Bangkok : Asian Institute of Technology, 1994)
This thesis study relates to the one of the major problem in implementing mixed model assembly line under Just In Time Production System. The problem is to generate a level schedule. The study is intended to serve the need of comparing the existing procedure under different assumption so as to improve/design new procedure with more assumption relaxed. A number of researchers have formulated the problem in a number of different way. A number of heuristic are also available to this complex mathematical problem. These mathematical formulations and heuristics are studied in detail here. Using computer program and hypothetically generated data the existing solution procedures are studied and compared with respect to their computational requirement and efficiency. The assumption regarding the single level problem is examined in detail. A small model with complete object oriented feature is also built. The model consists of complete independent work centers module working under Just In Time principle which can be used for building other model. Using this model, the heuristic's assumptions are tested. A way of using level schedule for the company where these can not be used due to large set up time and low cycle time is also suggested.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Just-in-time systems